EFISIENSI PEMASARAN KARET RAKYAT DI KECAMATAN DUSUN TENGAH KABUPATEN BARITO TIMUR - Sujarwo Sujarwo; Sri Umi Lestari (Universitas Tribhuwana Tunggadewi, 2007)
Objectives of this study were to elucidate efficiency level of rubber marketing at Dusun Tengah District, Barito Timur Regency. The study was conducted at. 60 farmers were randomly selected from three villages of Unsum, Lenggang and Puri, Dusun Tengah District. Samples of marketing agencies were selected based on non probability sampling method. Data analyses were analysis of profit function, and analysis of marketing, as well as descriptive analysis on market structure, performance and conduct to qualitatively measure marketing efficiency. Results of the study showed that there we two marketing channels in the study area, i.e. channel 1: Farmer –trader 1 –trader II (distributor) – rubber processing factory, and channel 2: Farmer –trader II (distributor)- rubber processing factory. Analysis of marketing margin indicated that price share received by farmers was 67,35%, whereas that received by trader I was 79,59%, and that received by trader II (distributor) was 100%. Marketing margin was not evenly distributed in between trader I and trader II (distributor) as trader II received the highest margin of 40,94%